Distribution Analysis Active Small and Medium Industries Bogor City Using K-means Clustering - Siska Andriani; Faradilla Rizqiyyah; Rahmat H A Asir (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2023)
Small and Medium Industries (IKM) is one sector that contributes to driving economic growth, one of which is in West Java province, Bogor city. The number of active IKM in the city of Bogor in 2021 based on the survey results was 1,189, while in 2022 the number of small and medium industries (IKM) active in the city of Bogor based on the survey results was 1,766. The purpose of this study was conducted to determine the distribution of active small and medium industries (IKM) in Bogor city. So, this research can provide solutions related to the government or agencies to assist in building and developing IKM. In this research, the method used is the Knowledge Discovery in Database method, Where the stages are data selection, pre-processing, transformation, data mining and evaluation. Determination of the number of clusters is done using the elbow method. After determining with Elbow, the data will be represented using K-means clustering. The results of the K-means clustering algorithm yield 3 clusters, with each cluster 0 criterion being the distribution of low IKM with a total of 45 sub-districts. Cluster 1 is the distribution of medium IKM with the number of sub-districts is 14, and cluster 2 is the distribution of high IKM with the number of sub-districts totaling 9. The evaluation in this study used the silhouette coefficient method, from the data used it produced a cluster value of 0.56 which means that it is included in the clustering criteria with a good structure.